Fracture toughness of a resin composite-ceramic interface - Hooshmand T.; Keshvad A.; Moharamzadeh K. Dentist (Tehran University of Medical Sciences, 2004)
Statement of Problem: In a previous study it was reported that a durable resin-ceramic tensile bond could be obtained by an appropriate silane application without the need for HF acid etching the ceramic surface. Evaluation of the appropriate application of silane by other test methods seems to be necessary. Purpose: The purpose of this study was to compare the interfacial fracture toughness of smooth and roughened ceramic surfaces bonded with a luting resin. Materials and Methods: Ceramic discs of 10 mm in diameter and 2 mm in thickness were prepared. Four different surface preparations (n=10) were carried out consisting of (1) ceramic surface polished to a 1µm finish, (2) gritblasted with 50µm alumina, (3) etched with 10% HF for 2 min, and (4) gritblasted and etched. The ceramic discs were then embedded in PMMA resin. For the adhesive area, the discs were masked with Teflon tapes. A circular hole with diameter of 3 mm and chevron-shaped with a 90° angle was punched into a piece of Teflon tape. The exposed ceramic surfaces were treated by an optimised silane treatment followed by an unfilled resin and then a luting resin cylinder of 4mm in diameter and 11 mm in length was built. Specimens were stored in two different storage conditions: (A): Distilled water at 37°C for 24 hours and (B): Distilled water at 37°C for 30 days. The interfacial fracture toughness (GIC) was measured at a cross-head speed of 1 mm/min. The mode of failure was examined under a stereo-zoom microscope and fracture surfaces were examined under Scanning Electron Microscope. Results: The mean interfacial fracture toughness values were; Group A: 1) 317.1±114.8, 2) 304.5±109.2, 3) 364.5±169.8, and 4) 379.4±127.8 J/m2±SD. Group B: 1) 255.6±134.4, 2) 648.0±185.1, 3) 629.3±182.6 and 4) 639.9 ±489.0 J/m2±SD. One way Analysis of Variance showed that there was no statistically significant difference in the mean interfacial fracture toughness for groups A1-A4 (P>0.05). However, the mean interfacial fracture toughness for group B1 was significantly different from that for groups B2, B3 and B4 (P<0.05). Independent-ٍٍٍSamples T-Test results showed that there was a significant increase in the GIC mean value for groups B2 and B3 after 30 days water storage (P<0.05). The modes of failure were predominantly interfacial or cohesive within the resin. Conclusions: The fracture toughness test method used in this study would be appropriate for analysis of the adhesive zone of resin-ceramic systems. From the results, it can be concluded that micro-mechanical retention by gritblasting the ceramic surfaces could be sufficient with no need for HF acid etching the ceramic surfaces when an appropriate silane application procedure is used.